(untitled) (Castilla. Estudios de Literatura, 2018)
The present work analyzes the first writings of Gómez de la Serna from its unique theoretical vocation. Here we provide new insights on the shape of the author taking into account new critical theories. Based on Nietzsche’s influence, interactions with psychoanalysis and links with french literature, we connect some poststructuralist propositions with some rising issues in Ramón’s literature: the crisis of the subject, the artist’s way of looking and the textual writing as a space of author’s displacement. This study reveals a writing that deconstructs its limits and removes its origin in order to emphasize the unspectedly revolutionary and theoretical significance of these texts.